Detection of Dental Caries' and Dermatoglyphics' Association with Relative Enamel Thickness Using CBCT Images in Saudi Subpopulation: A Novel Approach. (26th July 2021) - Dawasaz, A. A.; Alshahrani, Ibrahim; Yassin, Syed M.; Syed, Sadatullah; Hameed, Mohammad Shahul; Baig, Fawaz; Togoo, Rafi Ahmad; Master, Luqman
Abstract : Background . Dental caries is the localized destruction of dental hard tissues (enamel and dentine). Decayed, Missing, and Filled Teeth (DMFT) index is the most commonly used dental caries index. Thickness of the outermost part of the tooth called the enamel is determined by the rate of deposition of enamel proteins. Relative enamel thickness (RET) gives a measure of enamel thickness with respect to dentine. Dental caries is influenced by a genetically determined factor called dermatoglyphics (DG). As the genes responsible for RET and DG lie on the same chromosome and develop during the same time of intrauterine life, it is biologically plausible to correlate RET and DG. Aims . This study consists of two primary aims: (1) to assess RET using cone beam computed tomography images and correlate it with caries and (2) to correlate RET with DG. Materials and Methods . 148 dental subjects were assessed for DMFT caries score and were categorized as Group 1 with DMFT = 0 and Group 2 with DMFT ≥ 1 . Following this, their DG pattern was recorded digitally. The CBCT images of these subjects were assessed for RET, and the data were analyzed statistically. Results . Mean RET in our sample population is 18.45 (SD 3.79) while mean DMFT is 5.34 (SD 5.13). Mean RET in Group 1 subjects was 19.82 (SD 4.05) while that in the Group 2 was 17.68 (SD 3.43). RET and DMFT showed a statistically significant negative correlation (p = 0.007 ). The "Single Loop" DG characteristic showed a statistically significant difference between males and females (p = 0.031 ). The "Simple Arch" type of DG was positively correlated with RET. Conclusion . This is the first in vivo study to assess RET using CBCT images and correlate with DMFT and DG. RET is inversely related to DMFT while directly proportional to the "Simple arch" DG pattern. Males and females differed in their "Single Loop" DG characteristic.